Hydrogel microneedle patch based on three-dimensional framework structure, its preparation method and application
The hydrogel microneedle patch with a three-dimensional skeletal structure addresses preparation inefficiencies by using polyvinyl alcohol and acrylic resin, achieving enhanced mechanical strength and performance for controlled drug delivery and biomolecule extraction.
Patent Information
- Application Number
- JP2024527472
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-06-09
- Filing Date
- 2023-06-07
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-06-07
AI Technical Summary
Existing hydrogel microneedle technologies face challenges in efficient preparation due to time-consuming cross-linking processes, which limit their industrial applicability and drug stability, and they lack mechanical strength for effective puncturing and swelling performance.
A hydrogel microneedle patch based on a three-dimensional skeletal structure using polyvinyl alcohol and acrylic resin water dispersion, with a specific mass ratio and cross-linking methods like infrared irradiation, provides mechanical strength and enhances swelling and puncturing performance.
The method allows for a simple, fast, and efficient preparation of hydrogel microneedles with excellent swelling and puncturing capabilities, facilitating controlled drug delivery and extraction of biomolecules.
Smart Images

Figure 2024546025000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of transdermal delivery, more particularly to a hydrogel microneedle patch based on a three-dimensional framework structure and its preparation method and application. [Background technology]
[0002] Hydrogel microneedles are a microneedle technology that absorbs interstitial skin fluid in a body fluid environment to expand the needle body and promote drug release, but the matrix itself does not dissolve and can be completely removed after drug release is complete, and it has the advantages of being able to control drug release by adjusting the crosslinking strength of the hydrogel network, no matrix or auxiliary materials remain in the body after use, and higher biological safety. First reported in 2010, hydrogel microneedles can quickly absorb the expansion of tissue fluid after acting on the skin, and can maintain the open state of the skin microchannels for a long time, thus broadening their application field. 1) Hydrogel microneedles can replace single crystal silicon solid microneedles as a transdermal penetration enhancer; 2) Hydrogel microneedles can be used in combination with traditional drug-loaded transdermal preparations to improve the effective transdermal drug delivery efficiency of traditional skin preparations such as solutions, emulsions, patches, and gels; 3) Hydrogel microneedles can be used as drug carriers, and have the characteristics of directly loading active ingredients, having a large drug loading amount, and controlling the crosslinking degree inside the system to realize the control of the drug release rate; 4) Hydrogel microneedles can be used for the rapid detection and extraction of biomolecules in interstitial fluid, and have significant efficiency and cost advantages. Compared with metal and single crystal silicon solid microneedles, hydrogel microneedles have better material toughness, and there is no need to worry about the risk of the needle tip breaking and remaining in the skin during use; and compared with dissolving microneedles, hydrogel microneedles do not dissolve or decompose in a body fluid environment, and there is no need to worry about the problem of polymer accumulation in the body due to long-term use, making their use more convenient, safe and reliable.
[0003] Most of the hydrogel microneedles reported so far are crosslinked microneedles obtained by utilizing hydrogen bonding between polymer chains or ester formation reactions. The Jin Tuo Project Group of Shanghai Jiao Tong University prepared polyvinyl alcohol (PVA) hydrogel microneedles by repeated freezing and thawing process of freezing at -20℃ and thawing at 4℃, which can effectively deliver biopolymer drugs. However, the preparation of the microneedles requires a crosslinking process of repeated freezing and thawing, which is time-consuming and complicated, and is not suitable for industrialized preparation. The Donnelly Project Group of Queen's University of England studied the process of polymethyl vinyl ether / maleic anhydride copolymer (PMVE / MA) and polyethylene glycol (PEG) crosslinked at high temperature of 80℃ or under microwave conditions to form esters. They prepared super hydrogel microneedles with a swelling rate of up to 1600%, which can deliver drugs of different molecular weights through the transdermal route. However, the ester formation crosslinking process of the microneedles must be reacted at 80℃ for 24 hours or crosslinked in a microwave environment for 8 hours, which results in low preparation efficiency of the microneedles and disadvantages for mass production. In addition, the high temperature preparation conditions are prone to destroy the stability of the drugs, limiting the scope of application of the drugs. Summary of the Invention [Problem to be solved by the invention]
[0004] The first object of the present invention is to provide a hydrogel microneedle patch based on a three-dimensional skeletal structure, which utilizes the skeletal structure of an acrylic resin aqueous dispersion to surround a polyvinyl alcohol gel with relatively low cohesive strength, and the polyvinyl alcohol imparts a certain mechanical strength to the acrylic resin aqueous dispersion, which has no mechanical strength, thereby preparing a hydrogel microneedle patch that simultaneously has excellent swelling performance and puncture performance.
[0005] The second objective of the present invention is to provide a method for preparing a hydrogel microneedle patch based on a three-dimensional skeletal structure, which can prepare hydrogel microneedles under natural drying needling conditions, overcomes the limitations on crosslinking conditions in the prior art, and has the advantages of a simple microneedle preparation process, easy operation, and fast needling speed.
[0006] The third object of the present invention is to provide an application of a hydrogel microneedle patch based on a three-dimensional scaffold structure. [Means for solving the problem]
[0007] In order to achieve the first object, the present invention adopts the following technical solutions: A hydrogel microneedle patch based on a three-dimensional skeletal structure, the microneedle patch comprising microneedles, The raw materials of the microneedles include polyvinyl alcohol and an acrylic resin water dispersion, The acrylic resin water dispersion is uniformly mixed with polyvinyl alcohol and molded to obtain the microneedles.
[0008] Furthermore, in the microneedle patch, the acrylate resin aqueous dispersion surrounds a gel formed of polyvinyl alcohol as a skeletal structure.
[0009] Furthermore, the mass ratio of the polyvinyl alcohol to the acrylic resin water dispersion is 5-50:0.1-10.
[0010] It will further be understood that the microneedle structure includes a tip and a base, which may be molded integrally or separately.
[0011] Furthermore, the hydrogel microneedle patch further includes a backing, which is combined with the base.
[0012] In addition, functional additives, active substances, etc. can be added to the hydrogel microneedle patch according to actual needs. For example, in the hydrogel microneedle patch, the backing is a hollow aqueous adhesive patch, which plays the role of fixing the microneedle to the skin, and the active substance can be added to the middle cavity, that is, the active substance directly contacts the microneedle base; the other is a sticky sponge backing, which has good adhesion and drug carrying properties and carries the active substance.
[0013] Furthermore, the polyvinyl alcohol is a polyvinyl alcohol with a high alcohol decomposition degree, and the alcohol decomposition degree of the polyvinyl alcohol is 98% or more.
[0014] The acrylic resin water dispersion is an aqueous system in which water is used as a dispersion medium and acrylic resin is dispersed in water as solid or semi-solid spherical or spherical particles of 100 to 1000 nm, and it swells limitedly in biological media to form a dense three-dimensional skeletal structure. Polyvinyl alcohol with a high alcohol decomposition degree and high molecular weight is a swelling hydrogel material. In the process of drying the microneedle solution on the needle, hydrogen bonding action is formed within and between the polyvinyl alcohol molecules, and after encountering water, some of the polyvinyl alcohol forms hydrogen bonds with water molecules, weakening the hydrogen bonding action inside the polyvinyl alcohol molecules and reducing the cohesive force of the microneedle, and after swelling in water, the microneedle gels and cannot be completely removed from the skin. Based on the properties of the above two types of materials, the present invention mixes the two evenly and uses the skeletal structure of the acrylic resin water dispersion to surround the polyvinyl alcohol gel with a relatively low cohesive force, and polyvinyl alcohol imparts a certain mechanical strength to the acrylic resin water dispersion, which has no mechanical strength, to prepare a hydrogel microneedle preparation that has excellent swelling performance and puncture performance at the same time.
[0015] Furthermore, the acrylic resin water dispersion system is a mixture of one or more of an acrylic resin, an emulsifier, a preservative, an alkalizing agent, an organic solvent, and purified water.
[0016] Furthermore, the acrylic resin is one or a mixture of several selected from ethyl acrylate, methyl methacrylate, methacrylic acid trimethylamine ethyl chloride, methyl acrylate, and methacrylic acid.
[0017] Furthermore, the emulsifier is one or a mixture of several selected from stearyl alcohol polyether-2, nonylphenol ethoxylate, sodium lauryl sulfate, and polysorbate 80.
[0018] Furthermore, the preservative is one or a mixture of several selected from sorbic acid, benzoic acid, dehydroacetic acid, and methylparaben.
[0019] Furthermore, the alkalizing agent is one or a mixture of several selected from sodium hydroxide, potassium hydroxide, sodium bicarbonate, and ethanolamine.
[0020] Furthermore, the organic solvent is one or a mixture of two or more selected from ethanol and butanediol.
[0021] Furthermore, in the acrylic resin aqueous dispersion, the acrylic resin is one or a mixture of several selected from a copolymer of ethyl acrylate and methyl methacrylate in a molar ratio of 2:1, a copolymer of methacrylic acid, methyl acrylate, and methyl methacrylate in a molar ratio of 1:1:1, a copolymer of ethyl acrylate, methyl methacrylate, and trimethylaminoethyl methacrylate chloride in a molar ratio of 1:2:0.1, a copolymer of ethyl acrylate, methyl methacrylate, and trimethylaminoethyl methacrylate chloride in a molar ratio of 1:2:0.2, and a copolymer of methacrylic acid and ethyl acrylate in a molar ratio of 1:1.
[0022] Additionally, the microneedles further include a porogen.
[0023] Additionally, the porogen is located within an aqueous acrylic resin dispersion and / or polyvinyl alcohol.
[0024] Furthermore, the mass percentage content of the porogen in the microneedles is 0.1 to 10 wt %.
[0025] Furthermore, the porogen is one or a mixture of several selected from polyvinylpyrrolidone, calcium hydrogen phosphate, sodium hydrogen carbonate, sodium carbonate, trehalose, fructose, sorbitol, mannitol, xylitol, galactose, magnesium chloride, calcium chloride, and zinc chloride.
[0026] Porogens are small molecule substances that can be dissolved into the three-dimensional framework, which is advantageous for expanding the network gaps inside the microneedle, forming a larger drug delivery space, and for drugs with large molecular weights such as proteins, larger channels are advantageous for high-speed transport of drugs. By controlling the degree of PVA crosslinking, the degree of density of the three-dimensional network can be controlled to control the drug delivery rate, while controlling the use of porogens can control the delivery of drugs with different properties. In addition, during the infrared crosslinking process, if the degree of PVA crosslinking becomes too high, the edge of the microneedle may become curled, and adding polyvinylpyrrolidone not only functions as a porogen but also improves the flatness of the microneedle.
[0027] In order to achieve the second object, the present invention adopts the following technical solutions: A method for preparing a hydrogel microneedle patch based on a three-dimensional scaffold structure, comprising: preparing an aqueous solution of polyvinyl alcohol; The method includes the steps of dissolving the polyvinyl alcohol aqueous solution at high temperature, adding an acrylic resin aqueous dispersion, mixing uniformly to obtain a mixed aqueous solution, removing air bubbles, molding, and crosslinking to obtain the hydrogel microneedle patch.
[0028] Furthermore, the crosslinking process is one selected from infrared radiation crosslinking, physical freeze-thaw crosslinking, chemical agent crosslinking, annealing treatment crosslinking, microwave-assisted crosslinking, and radiation crosslinking.
[0029] Furthermore, in the infrared radiation crosslinking, the infrared radiation has a wavelength of 1000 to 5000 nm.
[0030] Furthermore, in the mixed aqueous solution, the mass percentage content of polyvinyl alcohol is 5 to 50 wt %.
[0031] Furthermore, in the mixed aqueous solution, the mass percentage content of the acrylic resin water dispersion is 0.1 to 10 wt %.
[0032] To achieve the third objective, the present invention further provides an application of the hydrogel microneedle patch in transdermal delivery of active materials.
[0033] Furthermore, the above-mentioned transdermal delivery methods include using a transdermal penetration enhancer, combining with a drug-carrying patch, or directly loading one of the drugs.
[0034] The present invention further relates to the application of the hydrogel microneedle patch in extracting biomolecules from skin interstitial fluid.
[0035] In addition, the hydrogel microneedle patch can exert a skin perforating effect, function as a percutaneous penetration enhancer, and promote the percutaneous penetration of active ingredients. Specific usage methods can be referred to the usage methods of conventional metal and single crystal silicon solid microneedles, and the description is omitted here.
[0036] Furthermore, the hydrogel microneedle patch can be used in combination with solutions, emulsions, creams, gels, and patches carrying active ingredients.Specific usage methods can be referred to the usage methods of conventional hydrogel microneedle patches, and the description is omitted here.
[0037] Furthermore, the hydrogel microneedle patch can be directly loaded with active ingredients, allowing intradermal administration.
[0038] Furthermore, the hydrogel microneedle patch can absorb tissue fluid, thereby realizing the extraction of biomolecules in skin interstitial fluid.
[0039] Furthermore, the active substance is one or more selected from small molecule drugs, herbal medicine extracts, polypeptides, proteins, and vaccines. Effect of the Invention
[0040] In the hydrogel microneedle patch provided by the present invention, the skeletal structure of the acrylic resin aqueous dispersion is used to surround the polyvinyl alcohol gel with relatively low cohesive force, and the polyvinyl alcohol imparts a certain strength to the acrylic resin aqueous dispersion that lacks mechanical strength, thereby preparing a hydrogel microneedle preparation that simultaneously has excellent swelling performance and puncture performance. In the preparation method of the present invention, the specific acrylic resin aqueous dispersion and polyvinyl alcohol are selected, so that a new crosslinking method can be adopted, and the hydrogel microneedle can be prepared under natural drying needle attachment conditions, which has the advantages of a simple microneedle preparation process, easy operation, and fast needle attachment speed. [Brief description of the drawings]
[0041] Specific embodiments of the present invention will be described in more detail below with reference to the drawings. [Figure 1] 1 shows schematic diagrams of four application forms of the hydrogel microneedle patch of the present invention. [Diagram 2] FIG. 1A shows a schematic diagram of the structure of the hydrogel microneedle patch of the present invention, and FIG. 1B shows a schematic diagram of the structure after absorbing body fluids and swelling, and the internal structure. [Diagram 3] FIG. 2 shows a topography diagram of the hydrogel microneedle patch of Example 1 of the present invention taken under a stereomicroscope. [Figure 4] FIG. 2 shows a skin puncture profile of the hydrogel microneedle patch of Example 1 of the present invention. [Diagram 5]FIG. 1 shows a comparative topography of the hydrogel microneedle patch of Example 2 of the present invention before (left) and after (right) swelling. [Figure 6] 1 shows the cumulative transdermal permeability of the skin surface after perforation with a hydrogel microneedle of the azelaic acid and matrine aqueous solution of Example 20 of the present invention. [Figure 7] 1 shows the cumulative transdermal permeability after using a combination of an aqueous solution of azelaic acid and matrine and a hydrogel microneedle patch of Example 21 of the present invention on the skin surface. [Figure 8] In Example 22 of the present invention, the cumulative transdermal permeation amount after using a combination of a commercially available 15% azelaic acid gel and a hydrogel microneedle patch on the skin surface is shown. [Figure 9] This shows the cumulative transdermal permeability after a hydrogel microneedle patch directly loaded with azelaic acid and matrine in Example 23 of the present invention was applied to the skin. [Figure 10] 2 shows Propionibacterium acnes extracted from the skin of a volunteer suffering from acne using the hydrogel microneedle of Example 24 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0042] In order to more clearly explain the present invention, the present invention will be further described below in conjunction with preferred embodiments and drawings. In the drawings, similar components are designated by the same reference numerals. It will be understood by those skilled in the art that the contents specifically described below are illustrative rather than limiting, and thus should not limit the scope of protection of the present invention.
[0043] Example 1 Preparation and puncture effect of hydrogel microneedle patch 17mL of ultrapure water was measured using a measuring cylinder, 2.2g (11wt%) of polyvinyl alcohol was added, and the mixture was placed in an oven at 90℃ for high-temperature dissolution to obtain an aqueous polyvinyl alcohol solution. 0.8g (4wt%) of an acrylic resin water dispersion (a copolymer of ethyl acrylate and methyl methacrylate with a molar ratio of 2:1) was weighed and added to the aqueous polyvinyl alcohol solution, which was then stirred uniformly to remove air bubbles. Microneedles were prepared using a mold method, and the microneedles were dried to form a film, after which the hydrogel microneedle patch was obtained. The structure of the hydrogel microneedle patch is shown in Figure 2a, and the structure and internal structure of the hydrogel microneedle patch after swelling due to absorption of body fluids are shown in Figure 2b.
[0044] The hydrogel microneedle patch was placed under a stereomicroscope to observe the topography of the microneedle, and the skin puncture performance of the microneedle was tested by an in vitro puncture test of in vitro pig skin. The specific operation is as follows: the frozen in vitro pig skin (hair removal, skin thickness 600 μm) was taken out of a refrigerator at -20°C, and after natural thawing at room temperature, a 1 cm x 1 cm area was cut out using a scalpel, and the moisture on the stratum corneum side was absorbed using filter paper, and the stratum corneum side was placed on the surface of a silica gel mold with the skin stratum corneum side facing up. The microneedle was applied to the skin for 20 s using a needle feed device (20 N / cm2), the microneedle was peeled off, and the skin was stained with 4 mg / mL trypan blue dye for 30 min. After the dyeing was completed, a cotton swab was used to wipe off the excess dye on the skin surface, and it was observed that a complete pinhole array was formed on the skin. The results are shown in Figures 3 and 4. The prepared hydrogel microneedles have a complete needle body topography, the needle tips are sharp and rich, and have good skin puncture ability.
[0045] Example 2 Preparation of porogen-trehalose-containing hydrogel microneedle patches Using a measuring cylinder, measure out 16.2 mL of ultrapure water, add 2.4 g (12 wt%) of polyvinyl alcohol, and place in a 90°C oven to dissolve at high temperature to obtain a polyvinyl alcohol aqueous solution. Then, measure out 1.4 g (7 wt%) of an acrylic resin water dispersion (a copolymer of ethyl acrylate and methyl methacrylate with a molar ratio of 2:1) and add it to the polyvinyl alcohol aqueous solution, stir uniformly, and remove air bubbles. Microneedles were prepared using a mold method, and after the microneedles were dried and formed into a film, they were placed in a phosphate buffer solution with a pH of 7.4 and allowed to swell for 8 hours at 37°C. They were then taken out and observed, and the topographical changes of the microneedles before and after swelling were compared. The results are shown in Figure 5. The results show that after swelling for 8 hours, the water absorption volume of the microneedles increases significantly, but the microstructure of the needle tip, etc. is still good, indicating that the microneedles have good swelling performance.
[0046] (Examples 3 to 14) Preparation of hydrogel microneedle patches containing other types of porogens According to the preparation method of microneedles in Example 2, the hydrogel microneedle formulations containing different types of porogens in Table 1 were combined to prepare microneedle solutions to obtain a series of hydrogel microneedle patches. The microneedles of each formulation were placed in a phosphate buffer solution with pH=7.4, and observed to see whether they retained the needle tip integrity after swelling at 37°C for 8 hours to determine whether the microneedles had swelling performance. The results are shown in Table 1, which show that the hydrogel microneedles of each formulation all have good in vitro swelling properties.
[0047] [Table 1]
[0048] Example 15 Preparation of infrared crosslinkable hydrogel microneedle patches Using a measuring cylinder, 16.2 mL of ultrapure water was measured out, 2.8 g (14 wt%) of polyvinyl alcohol was added, and the mixture was placed in an oven at 90°C for high-temperature dissolution to obtain an aqueous polyvinyl alcohol solution. 1 g (5 wt%) of an acrylic resin water dispersion (a copolymer of methacrylic acid and methyl acrylate with a molar ratio of 1:1:1) was weighed out and added to the aqueous polyvinyl alcohol solution, and the mixture was stirred uniformly to remove air bubbles. Microneedles were prepared using a mold method, and the microneedles were dried to form a film. After that, the microneedles were placed under an infrared lamp with a wavelength of 2400 to 3500 nm and irradiated at 70°C for 1 minute to promote crosslinking. The microneedles that were not crosslinked by infrared and the microneedles that were crosslinked by infrared were taken, weighed, and then placed in a phosphate buffer solution with pH=7.4 to swell at 37℃ for 8h, then taken out, absorbed the moisture on the surface of the microneedles using filter paper, and weighed again. The effect of infrared crosslinking on the swelling rate of the microneedles was calculated using the formula: swelling rate=(weight of microneedles after swelling-weight of microneedles before swelling) / weight of microneedles before swelling*100%. The results are shown in Table 2. The results show that the swelling rate of the microneedles by the infrared crosslinking group is significantly reduced, and the cohesive force between polyvinyl alcohol molecules is further improved by infrared irradiation, forming more hydrogen bonds, thereby reducing the swelling rate of the microneedles. Based on the network formed by the existing PVA and water dispersion, it was discovered that PVA itself can achieve its own crosslinking by infrared light irradiation. Although the PVA is controlled in the network skeleton of the water dispersion to ensure that it still has a perfect needle shape after swelling, in fact, due to the gel nature of PVA, a small amount of PVA may dissolve in the solvent medium. If we want to further control the dissolution of PVA, we can achieve a higher crosslinking degree by further strengthening the crosslinking between PVA molecules.
[0049] [Table 2]
[0050] Example 16 Preparation of freeze-thaw crosslinked hydrogel microneedle patches Using a measuring cylinder, 16.8 mL of ultrapure water was measured out, 3 g (15 wt%) of polyvinyl alcohol was added, and the mixture was placed in a 90°C oven for high-temperature dissolution to obtain an aqueous polyvinyl alcohol solution. 0.2 g (1 wt%) of an acrylic resin water dispersion (a copolymer of methacrylic acid and methyl acrylate with a molar ratio of 1:1:1) was weighed out and added to the aqueous polyvinyl alcohol solution, and the mixture was stirred uniformly to remove air bubbles. Microneedles were prepared using a mold method, and after the microneedles were molded, the mold was placed in a refrigerator at -20°C for freezing treatment for 8 hours, and then placed in a refrigerator at 4°C for melting treatment for 8 hours. After the above circulation was repeated twice, a crosslinked hydrogel microneedle patch was obtained. The microneedles that were not freeze-thaw crosslinked and the microneedles that were freeze-thaw crosslinked were taken, weighed, and placed in a phosphate buffer solution with a pH of 7.4 to swell at 37°C for 8 hours, then taken out, and the moisture on the surface of the microneedles was absorbed using filter paper, and weighed again. The effect of freeze-thaw crosslinking on the swelling rate of the microneedles was calculated using the formula: swelling rate = (weight of microneedles after swelling - weight of microneedles before swelling) / weight of microneedles before swelling * 100%, and the results are shown in Table 3. As a result, it was shown that the swelling rate of the microneedles due to freeze-thaw crosslinking was significantly reduced, and the repeated freezing and thawing further improved the cohesive force between polyvinyl alcohol molecules, forming more hydrogen bonds, and thereby reducing the swelling rate of the microneedles. Based on the network formed by the existing PVA and water dispersion, it was discovered that PVA itself can achieve its own crosslinking by repeated freezing and thawing treatment. Although the PVA is controlled in the network skeleton of the water dispersion to ensure that it still has a perfect needle shape after swelling, in fact, due to the gel nature of PVA, a small amount of PVA may dissolve in the solvent medium. If we want to further control the dissolution of PVA, we can achieve a higher crosslinking degree by further strengthening the crosslinking between PVA molecules.
[0051] [Table 3]
[0052] (Example 17) Preparation of chemically crosslinked hydrogel microneedle patches Using a measuring cylinder, 16.2 mL of ultrapure water was measured out, 2.4 g (12 wt%) of polyvinyl alcohol was added, and the mixture was placed in an oven at 90°C for high-temperature dissolution to obtain an aqueous polyvinyl alcohol solution. 1.2 g (6 wt%) of an acrylic resin water dispersion (a copolymer of methacrylic acid and methyl acrylate with a molar ratio of 1:1:1) was measured out and added to the aqueous polyvinyl alcohol solution, and 0.2 g (1 wt%) of glutaraldehyde was added as a crosslinking agent. The mixture was stirred uniformly to remove air bubbles, and microneedles were prepared using a mold method. After the microneedles were molded, a hydrogel microneedle patch was obtained that was crosslinked with a chemical agent. The non-crosslinked and crosslinked microneedles were taken, weighed, and then placed in a phosphate buffer solution with pH=7.4 to swell for 8 hours at 37℃. They were then taken out and used filter paper to absorb the moisture on the surface of the microneedles, and weighed again. The formula: swelling rate=(weight of microneedles after swelling-weight of microneedles before swelling) / weight of microneedles before swelling*100% was used to calculate the effect of crosslinking agent crosslinking on the swelling rate of the microneedles. The results are shown in Table 4. The results show that the swelling rate of the microneedles due to the crosslinking group is significantly reduced, and the chemical crosslinking agent can form a chemical bond with the hydroxyl group of polyvinyl alcohol, improving the degree of system crosslinking and thereby reducing the swelling rate of the microneedles. Based on the network formed by the existing PVA and aqueous dispersion, it was discovered that PVA itself can achieve its own crosslinking by the chemical crosslinking agent. Although the PVA is controlled in the network skeleton of the water dispersion to ensure that it still has a perfect needle shape after swelling, in fact, due to the gel nature of PVA, a small amount of PVA may dissolve in the solvent medium. If we want to further control the dissolution of PVA, we can achieve a higher crosslinking degree by further strengthening the crosslinking between PVA molecules.
[0053] [Table 4]
[0054] (Example 18) Preparation of microwave crosslinked hydrogel microneedle patches Using a measuring cylinder, 15.9 mL of ultrapure water was measured out, 4 g (20 wt%) of polyvinyl alcohol was added, and the mixture was placed in an oven at 90°C for high-temperature dissolution to obtain an aqueous polyvinyl alcohol solution. 0.1 g (0.5 wt%) of an acrylic resin water dispersion (a copolymer of methacrylic acid and methyl acrylate with a molar ratio of 1:1:1) was weighed out and added to the aqueous polyvinyl alcohol solution, and the mixture was stirred uniformly to remove air bubbles. Microneedles were prepared using a mold method, and the microneedles were dried to form a film, and then placed in a microwave box for 10 minutes for microwave treatment to promote crosslinking. The microneedles that were not crosslinked by microwave and the crosslinked microneedles were taken, weighed, and then placed in a phosphate buffer solution with a pH of 7.4 to swell for 8 hours at 37°C. They were then taken out and used filter paper to absorb the moisture on the surface of the microneedles, and weighed again. The formula: swelling rate = (weight of microneedles after swelling - weight of microneedles before swelling) / weight of microneedles before swelling * 100% was used to calculate the effect of microwave crosslinking on the swelling rate of the microneedles. The results are shown in Table 5. As a result, the swelling rate of the microneedles in the microwave crosslinking group was significantly reduced, and microwave crosslinking further improved the cohesive force between polyvinyl alcohol molecules, forming more hydrogen bonds, and thereby reducing the swelling rate of the microneedles. Based on the network formed by the existing PVA and water dispersion, it was discovered that PVA itself can achieve its own crosslinking by microwave treatment. Although the PVA is controlled in the network skeleton of the water dispersion to ensure that it still has a perfect needle shape after swelling, in fact, due to the gel nature of PVA, a small amount of PVA may dissolve in the solvent medium. If we want to further control the dissolution of PVA, we can achieve a higher crosslinking degree by further strengthening the crosslinking between PVA molecules.
[0055] [Table 5]
[0056] (Example 19) Preparation of electron beam irradiation crosslinked hydrogel microneedle patches Using a measuring cylinder, 15.2 mL of ultrapure water was measured out, 3.2 g (16 wt%) of polyvinyl alcohol was added, and the mixture was placed in an oven at 90°C for high-temperature dissolution to obtain an aqueous polyvinyl alcohol solution. 1.6 g (8 wt%) of an acrylic resin water dispersion (a copolymer of methacrylic acid and methyl acrylate with a molar ratio of 1:1:1) was measured out and added to the aqueous polyvinyl alcohol solution. The mixture was stirred uniformly to remove air bubbles, and a microneedle was prepared using a mold method. The microneedle was dried to form a film, and then irradiated with an electron beam for 20 minutes to promote crosslinking. The microneedles that were not crosslinked by radiation and the crosslinked microneedles were taken, weighed, and then placed in a phosphate buffer solution with a pH of 7.4 to swell at 37°C for 8 hours. They were then taken out, and the moisture on the surface of the microneedles was absorbed using filter paper, and weighed again. The effect of radiation crosslinking on the swelling rate of the microneedles was calculated using the formula: swelling rate = (weight of microneedles after swelling - weight of microneedles before swelling) / weight of microneedles before swelling * 100%. The results are shown in Table 6. As a result, the swelling rate of the microneedles due to the radiation crosslinking group was significantly reduced, and radiation crosslinking showed that the secondary carbon and tertiary carbon in the polyvinyl alcohol molecular chain formed hydroxyl radicals, and after the radiation was removed, the radicals formed chemical bond crosslinks through a two-group coupling reaction, thereby reducing the swelling rate of the microneedles. Based on the network formed by the existing PVA and aqueous dispersion, it was discovered that PVA itself can achieve its own crosslinking by electron beam irradiation. Although the PVA is controlled in the network skeleton of the water dispersion to ensure that it still has a perfect needle shape after swelling, in fact, due to the gel nature of PVA, a small amount of PVA may dissolve in the solvent medium. If we want to further control the dissolution of PVA, we can achieve a higher crosslinking degree by further strengthening the crosslinking between PVA molecules.
[0057] [Table 6]
[0058] (Example 20) Transdermal permeability of hydrogel microneedle patch as a percutaneous permeation enhancer for aqueous solutions of active ingredients Using a measuring cylinder, 16.4 mL of ultrapure water was measured, 2.4 g (12 wt%) of polyvinyl alcohol was added, and the mixture was placed in an oven at 90 °C for high-temperature dissolution to obtain a polyvinyl alcohol aqueous solution. 1.2 g (6 wt%) of acrylic resin water dispersion (ethyl acrylate and methyl methacrylate copolymer with a molar ratio of 2:1) was weighed and added to the polyvinyl alcohol aqueous solution, and the mixture was stirred uniformly to remove air bubbles. Microneedles were prepared using a mold method, and a hydrogel microneedle patch was obtained after drying. Aqueous solutions with mass contents of azelaic acid and matrine of 1% and 1.3%, respectively, were prepared as active ingredient solutions. The hydrogel microneedle was attached to the stratum corneum side of in vitro pig skin, and pressed for 20 seconds using a self-made needle feeder (20N / cm2), after which the microneedle patch was removed, the skin was fixed in a transdermal cup, 100μL of active ingredient aqueous solution was added to the dosing tank side, and the fully automatic transdermal meter was used to automatically sample at regular intervals, and the drug content in the receiving tank was analyzed using a high performance liquid chromatograph, and the cumulative transdermal permeability of the drug was obtained, and the results are shown in Figure 6. As a result, after using the hydrogel microneedle patch as a transdermal permeation promoter, the dosing microchannel on the skin surface could be effectively opened, and the transdermal permeation of the active ingredient aqueous solution was promoted. In a continuous 10-h in vitro transdermal permeation test, the cumulative delivery rates of azelaic acid and matrine were 14.90±3.77% and 12.30±2.95%, respectively. In addition, a blank control group was set up, in which the same volume of active ingredient solution was dropped onto the untreated intact skin stratum corneum side, and the skin was similarly fixed in a transdermal cup to conduct an in vitro transdermal permeability test. The results showed that neither azelaic acid nor matrine in the blank control group was able to effectively penetrate the stratum corneum barrier to enter the receiving pool within 10 hours, and the hydrogel microneedle patch was able to effectively exert the skin porosity effect, promoting the transdermal delivery of the active ingredient aqueous solution.
[0059] Example 21 Transdermal permeability of a combination of a hydrogel microneedle patch and an aqueous solution of an active ingredient Using a measuring cylinder, 16.4 mL of ultrapure water was measured, 2.4 g (12 wt%) of polyvinyl alcohol was added, and the mixture was placed in an oven at 90 °C for high-temperature dissolution to obtain a polyvinyl alcohol aqueous solution. 1.2 g (6 wt%) of acrylic resin water dispersion (ethyl acrylate and methyl methacrylate copolymer with a molar ratio of 2:1) was weighed and added to the polyvinyl alcohol aqueous solution, and the mixture was stirred uniformly to remove air bubbles. Microneedles were prepared using a mold method, and a hydrogel microneedle patch was obtained after drying. Aqueous solutions with mass contents of azelaic acid and matrine of 1% and 1.3%, respectively, were prepared as active ingredient solutions. The hydrogel microneedles were attached to the stratum corneum side of in vitro pig skin, and pressed for 20 seconds using a homemade needle feeder (20N / cm2), after which the microneedles were pierced into the skin. The skin with the microneedles attached was fixed in a transdermal cup, and 100μL of active ingredient aqueous solution was added. Automatic sampling was performed at regular intervals using a fully automatic transdermal meter. The drug content in the receiving tank was analyzed using a high performance liquid chromatograph, and the cumulative transdermal permeability of the drug was calculated. The results are shown in Figure 7. As a result, when using a hydrogel microneedle patch containing active ingredient aqueous solution, effective drug permeation can be achieved, and after 10h of continuous action, the cumulative permeability of azelaic acid and matrine was 29.42±2.43% and 27.51±1.57%, respectively. Water-soluble drugs with relatively poor transdermal permeability have good permeation efficiency in the field of transdermal delivery.
[0060] Example 22 Transdermal permeability of a combination of a hydrogel microneedle patch and an active ingredient gel Using a measuring cylinder, 16.4 mL of ultrapure water was measured out, 2.4 g (12 wt%) of polyvinyl alcohol was added, and the mixture was placed in an oven at 90°C for high-temperature dissolution to obtain an aqueous polyvinyl alcohol solution. 1.2 g (6 wt%) of an acrylic resin water dispersion (a copolymer of ethyl acrylate and methyl methacrylate with a molar ratio of 2:1) was then measured out and added to the aqueous polyvinyl alcohol solution. The mixture was stirred uniformly to remove air bubbles, and microneedles were prepared using a mold method. After drying, a hydrogel microneedle patch was obtained. A hydrogel microneedle was attached to the stratum corneum side of in vitro pig skin, and pressed for 20 seconds using a homemade needle feeder (20 N / cm2), after which the microneedle was pierced into the skin. The skin with the microneedle attached was fixed to a transdermal cup, and 100 μL of commercially available 15 (wt)% azelaic acid gel was added to the administration tank side. Automatic sampling was performed at regular intervals using a fully automatic transdermal meter. The drug content in the receiving tank was analyzed using a high-performance liquid chromatograph, and the cumulative transdermal permeability of the drug was calculated. The results are shown in Figure 8. As a result, when a commercially available azelaic acid gel formulation is used in combination with a hydrogel microneedle patch, effective permeation of the drug can be achieved, and it can be continuously acted for 10 h. The cumulative permeation amount of azelaic acid reaches 228 μg, and good transdermal penetration can be achieved compared to the commercially available formulation.
[0061] (Example 23) Transdermal permeability of hydrogel microneedle patches directly loaded with azelaic acid and matrine 15.58mL of ultrapure water was weighed out using a graduated cylinder, 2.4g (12wt%) of polyvinyl alcohol was added, and the mixture was placed in a 90℃ oven for high-temperature dissolution to obtain a polyvinyl alcohol aqueous solution. 2g (10wt%) of polyvinylpyrrolidone was weighed and added to the polyvinyl alcohol solution, and 0.02g (0.1wt%) of acrylic resin water dispersion (ethyl acrylate and methyl methacrylate copolymer with a molar ratio of 2:1) was weighed and added to the polyvinyl alcohol aqueous solution, which was then stirred uniformly to remove air bubbles and obtain a microneedle matrix solution. An aqueous solution of 1% azelaic acid and 1.3% matrine was prepared, and after the two active ingredients were completely dissolved, the active ingredient solution was mixed with the microneedle substrate solution to obtain a drug-loaded microneedle solution, air bubbles were removed, and microneedles were prepared using a mold method, and hydrogel microneedles loaded with azelaic acid and matrine were obtained after drying. The microneedles were placed under an infrared lamp at 70°C for 2 minutes to promote crosslinking of the microneedles. The microneedles were then attached to the stratum corneum of pig skin in vitro, and pressed for 20 seconds using a homemade needle feeder (20N / cm2), after which the microneedles were pierced into the skin. The skin with the microneedles attached was fixed in a transdermal cup, and automatically sampled at regular intervals using a fully automatic transdermal meter. The drug content in the receiving pool was analyzed using a high-performance liquid chromatograph, and the cumulative transdermal permeability of the drug was calculated. The results are shown in Figure 9. As a result, after 10 hours of continuous application, the cumulative transdermal permeability of azelaic acid and matrine base can both reach more than 50%, and the two drugs can maintain good synchronous release.
[0062] (Example 24) Hydrogel microneedle patch is used for extraction of Propionibacterium acnes in cutaneous acne Using a measuring cylinder, 16.4 mL of ultrapure water was measured out, 4 g (20 wt%) of polyvinyl alcohol was added, and the mixture was placed in an oven at 90°C for high-temperature dissolution to obtain an aqueous polyvinyl alcohol solution. 0.4 g (2 wt%) of an acrylic resin water dispersion (a copolymer of ethyl acrylate and methyl methacrylate with a molar ratio of 2:1) was measured out and added to the aqueous polyvinyl alcohol solution. The mixture was stirred uniformly to remove air bubbles, and a microneedle was prepared using a mold method. After drying, a hydrogel microneedle patch was obtained, and the hydrogel microneedle patch was placed under an ultraviolet lamp for sterilization overnight. The facial acne area of the volunteers with acne was disinfected with an alcohol swab, and then a sterile hydrogel microneedle patch was used to pierce the acne skin and keep it on for 3 minutes. After that, the microneedle patch was removed and the microneedle was placed in the previously prepared sterile thioglycolate liquid medium. At the same time, one hydrogel microneedle that did not contact the skin was taken as a blank control and directly placed in the sterile thioglycolate liquid medium. The two portions of the medium solution were placed in an anaerobic environment at 37°C for 72 hours and then removed to observe whether there was bacterial growth in the medium in the two culture bottles. A small amount of the medium in each bottle was dropped into a sterile Columbia agar solid medium, the medium was placed in an anaerobic environment at 37°C for 72 hours and then removed to observe the growth of colonies on the culture plate, and compared with the positive control--the purchased Propionibacterium acnes strain to determine whether the P. acnes was successfully extracted from the skin. The results are shown in Figure 9. The results showed that after the hydrogel microneedle was applied to the acne skin, the thioglycolate liquid medium became obviously turbid, indicating that bacteria were growing, whereas the medium in the hydrogel microneedle group that was not in contact with the skin remained clear, and no bacteria were present.In addition, after inoculation on blood agar culture plate, the hydrogel microneedle group after applied to the acne skin grew white colonies on the agar, with smooth colony surface, consistent with the colony morphology of the positive control group of Propionibacterium acnes, indicating that the hydrogel microneedle patch can be used to extract Propionibacterium acnes from acne skin.
[0063] The above examples of the present invention are merely illustrative to clearly explain the present invention, and are not intended to limit the embodiments of the present invention. In addition to the above description, those skilled in the art may make other different forms of changes or variations. It is not possible to cover all embodiments here, and obvious changes or variations due to the technical solutions of the present invention are included in the protection scope of the present invention.
Claims
1. A hydrogel microneedle patch based on a three-dimensional skeletal structure, the microneedle patch comprising microneedles, The raw materials of the microneedles include polyvinyl alcohol and an acrylic resin water dispersion, The acrylic resin aqueous dispersion is uniformly mixed with polyvinyl alcohol and molded to obtain the microneedle; Here, in the microneedle patch, the acrylate resin aqueous dispersion surrounds a gel formed of polyvinyl alcohol as a skeletal structure, which is a hydrogel microneedle patch based on a three-dimensional skeletal structure.
2. The hydrogel microneedle patch according to claim 1, wherein the polyvinyl alcohol is a high alcohol decomposition polyvinyl alcohol.
3. The hydrogel microneedle patch according to claim 2, characterized in that the alcohol decomposition degree of the polyvinyl alcohol is 98% or more.
4. The hydrogel microneedle patch of claim 1, wherein the acrylic resin aqueous dispersion system is a mixture of one or more of acrylic resin, emulsifier, preservative, alkalizing agent, organic solvent and purified water.
5. The hydrogel microneedle patch of claim 4, wherein the acrylic resin is one or a mixture of several selected from ethyl acrylate, methyl methacrylate, methacrylic acid trimethylamine ethyl chloride, methyl acrylate, and methacrylic acid.
6. The hydrogel microneedle patch according to claim 4, characterized in that the emulsifier is one or a mixture of several selected from stearyl alcohol polyether-2, nonylphenol ethoxylate, sodium lauryl sulfate, and polysorbate-80.
7. The hydrogel microneedle patch according to claim 4, characterized in that the preservative is one or a mixture of several selected from the group consisting of sorbic acid, benzoic acid, dehydroacetic acid, and methylparaben.
8. The hydrogel microneedle patch according to claim 4, characterized in that the alkaline agent is one or a mixture of several selected from sodium hydroxide, potassium hydroxide, sodium bicarbonate, and ethanolamine.
9. The hydrogel microneedle patch according to claim 4, wherein the organic solvent is one or a mixture of several selected from ethanol and butanediol.
10. The hydrogel microneedle patch of claim 1, characterized in that in the acrylic resin aqueous dispersion, the acrylic resin is one or a mixture of several selected from a copolymer of ethyl acrylate and methyl methacrylate in a molar ratio of 2:1, a copolymer of methacrylic acid, methyl acrylate, and methyl methacrylate in a molar ratio of 1:1:1, a copolymer of ethyl acrylate, methyl methacrylate, and trimethylaminoethyl methacrylate chloride in a molar ratio of 1:2:0.1, a copolymer of ethyl acrylate, methyl methacrylate, and trimethylaminoethyl methacrylate chloride in a molar ratio of 1:2:0.2, and a copolymer of methacrylic acid and ethyl acrylate in a molar ratio of 1:
1.
11. The hydrogel microneedle patch of claim 1, wherein the microneedles further comprise a porogen, the porogen being located within an acrylic resin aqueous dispersion and / or polyvinyl alcohol.
12. The hydrogel microneedle patch of claim 11, wherein the mass percentage content of the porogen in the microneedles is 0.1 to 10 wt %.
13. The hydrogel microneedle patch of claim 11, characterized in that the porogen is one or a mixture of several selected from polyvinylpyrrolidone, calcium hydrogen phosphate, sodium bicarbonate, sodium carbonate, trehalose, fructose, sorbitol, mannitol, xylitol, galactose, magnesium chloride, calcium chloride, and zinc chloride.
14. preparing an aqueous solution of polyvinyl alcohol; The method for preparing a hydrogel microneedle patch according to any one of claims 1 to 13, further comprising the steps of: dissolving the aqueous solution of polyvinyl alcohol at high temperature, adding an aqueous acrylic resin dispersion, mixing uniformly to obtain a mixed aqueous solution, removing air bubbles, molding, and crosslinking to obtain the hydrogel microneedle patch.
15. The preparation method according to claim 14, characterized in that the crosslinking is one selected from infrared light irradiation crosslinking, physical freezing and thawing crosslinking, chemical agent crosslinking, annealing treatment crosslinking, microwave-assisted crosslinking and radiation crosslinking.
16. The preparation method according to claim 15, characterized in that the infrared light wavelength of the infrared radiation crosslinking is 1000-5000 nm.
17. The preparation method according to claim 14, wherein in the mixed aqueous solution, the mass percentage content of polyvinyl alcohol is 5 to 50 wt %.
18. The preparation method according to claim 14, wherein the mass percentage content of the acrylic resin water dispersion in the mixed aqueous solution is 0.1 to 10 wt %.
Citation Information
Patent Citations
Hydrogel microneedle patch for collecting skin interstitial fluid and preparation method and application method thereof
CN110090044A
Strong hydrophilic microneedle base material, drug-loaded microneedle and application of drug-loaded microneedle in disease treatment
CN113426004A
Microneedle devices and production thereof
US20020082543A1
Devices and methods for transdermal treatment of basal cell carcinoma
US20180369136A1
